2015
DOI: 10.1021/acsami.5b06374
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Underwater Oil Adhesion on Superoleophobic Copper Films through Assembling n-Alkanoic Acids

Abstract: Controlling liquid adhesion on special wetting surface is significant in many practical applications. In this paper, an easy self-assembled monolayer technique was advanced to modify nanostructured copper substrates, and tunable adhesive underwater superoleophobic surfaces were prepared. The surface adhesion can be regulated by simply varying the chain length of the n-alkanoic acids, and the tunable adhesive properties can be ascribed to the combined action of surfaces nanostructures and related variation in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 50 publications
0
36
0
Order By: Relevance
“…Contrary to the fish scales, if the oil adhesion of a superoleophobic surface is very high rather than ultralow, the oil droplet will be able to stick to the surface no matter the substrate is tilted at any angle. Such high adhesive surface can be used to transport small oil droplet without any volume loss . Because of the important applications in manipulating oil droplets on the target materials, the multifunctional superoleophobic surfaces showing controllable adhesion (from low to high) to oil droplet have attracted growing interest among the researchers …”
Section: Femtosecond Laser‐induced Underwater Superoleophobicitymentioning
confidence: 99%
See 3 more Smart Citations
“…Contrary to the fish scales, if the oil adhesion of a superoleophobic surface is very high rather than ultralow, the oil droplet will be able to stick to the surface no matter the substrate is tilted at any angle. Such high adhesive surface can be used to transport small oil droplet without any volume loss . Because of the important applications in manipulating oil droplets on the target materials, the multifunctional superoleophobic surfaces showing controllable adhesion (from low to high) to oil droplet have attracted growing interest among the researchers …”
Section: Femtosecond Laser‐induced Underwater Superoleophobicitymentioning
confidence: 99%
“…The adhesion between the underwater oil droplet and the solid substrate is primarily determined by the wetting state of the droplet . The hierarchical periodic microislands fabricated at the scanning speed of 2 mm s −1 and the shift of scanning lines of 2 µm are rough enough.…”
Section: Femtosecond Laser‐induced Underwater Superoleophobicitymentioning
confidence: 99%
See 2 more Smart Citations
“…Zhang et al reported a series of underwater superoleophobic Ni/NiO surfaces with controlled oil adhesion by combining electrodeposition and heating techniques16. Cheng et al proposed a self-assembled monolayer technique to modify nanostructured copper substrates to prepare tuneable adhesive underwater superoleophobic surfaces17. However, these manufacturing processes are difficult to control, and the reported underwater superoleophobic surfaces only exhibit improved oil wettability, greatly limiting their application to underwater devices such as oil-repellent military submarines and amphibious military aircraft and tanks, which also require optical stealth.…”
mentioning
confidence: 99%